The other way around - Verdon, Frank P. (Radcliffe Press ; St. Martin's Press [distributor], 1996)
One hundred and fifty years after Charles Darwin completed his epic voyage in HMS Beagle, a research ship owned and operated by the UK's Natural Environment Research Council and bearing the name of the famous scientist began another global circumnavigation that would take her away from her home base for three and a half years. Unlike HMS Beagle, the Royal Research Ship (RRS) Charles Darwin would not be dedicated to the scientific endeavours of one man, but would support some two dozen scientific teams studying topics as diverse as the causes of El Nino, deep sea currents in the Indian Ocean, or the speed with which the Indian subcontinent moves towards Asia.